A Criminological Analysis of Homicide Committed by Husbands Against Their Wives - Ahmad Nizar Mohammad Syamwil; Dian Perwita Sari (AT-TAFAHUM: Journal of Law, 2018)
Cases of murder committed by husbands against wives are a serious problem in society. This study aims to analyze the factors causing the murder, as well as its impact on the victim's child. The method used is descriptive research using data from observations, documentation, and interviews with AKP Abner Saragih, one of the investigative teams handling the case. The results showed that the murder occurred due to jealousy and economic problems in the household. The perpetrator used a machete that had been prepared before hand, resulting in the death of his wife and serious injuries to the victim's child. The victim's children are currently being raised by the victim's family without their biological parents. The conclusion of this study is the need for serious handling of domestic homicide cases, as well as the importance of the role of law enforcement agencies in providing justice to victims. This research also provides suggestions for increasing public awareness about the importance of peaceful conflict resolution, as well as the need for psychological support for children who have been traumatized by a murder case in the family. It is hoped that the results of this study can provide a deeper understanding of the problem of domestic murder and contribute to preventing similar cases from occurring in the future.